HUBUNGAN ANTARA HBA1C DAN KADAR LIPID SERUM DENGAN DERAJAT BERAT RETINOPATI DIABETIKA - Refa, Safaruddin; Dewi, Nadia Artha (Fakultas Kedokteran Universitas Brawijaya, 2005)
Diabetic retinopathy is a leading cause of blindness in industrial world and is rapidly becoming an important cause in developing countries. Many factors related with theseverity of diabetic retinopathy, such as HbA1c and serum lipid. The study wants to know whether those factors have any correlation with the severity of diabetic retinopathy or not. The objective this study was to determine the correlation between HbA1c and serum lipid with the severity of diabetic retinopathy. An analytic cross sectional observational research had been done at Saiful Anwar hospital. The samples (diabetic retinopaty patients) were taken with consecutive sampling. These patient underwent funduscopy, fundus photography, laboratory examination including HbA1c, serum lipid (total serum cholesterol, LDL, HDL, triglycerides), and blood glucose. These patient were questioned about risk factors previously determined by the authors. The laboratory findings were thease are compared to the severity of diabetic retinopathy.